The Occurrence and Evaluation of Risk Factors Associated with Cataract in People of Pakistan: A Clinical Study - Yasir Nawaz; Saba Munir; Ambar Ayoub; Alia Iqbal; Fouzia Tanvir; Muhammad Luqman (Journal of Nature and Science of Medicine)
Background: A cataract is the clouding of the lens in the eyes, and it is a major cause of blindness worldwide, especially in tropical regions where a significant portion of the population resides in developing nations.